Models and software of study process data analysis - Janilionis, Vytautas; Ruzgas, Tomas (Lietuvos matematikos rinkinys, 2001)
The models of study process data analysis and statistical software for decision-making support are presented in this paper. The models and software were developed using applied statistics methods (descriptive statistics, analysis of variance, nonparametric tests, cluster analysis, correlation and logistic regression analysis) as well as data warehousing, multidimensional reporting, visualisation, object progranuning technologies and software SAS. The developed system is used for the analysis of study process data of Kaunas University of Technology. It enables to analyse the relationships and dependencies between various factors (e.g. study areas, faculties, study modules groups, form of studies, credits, weighted averages of the exams grades, grades of study modules or their groups etc.) and use the results for the effective decision-making.